2017
DOI: 10.1088/1361-6595/aa68d0
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘Issues in the understanding of negative ion extraction for fusion’

Abstract: The discussed paper strongly criticizes the capability of 3D PIC codes for describing the extraction physics of negative hydrogen ions generated via the surface conversion process using caesium. A strong disagreement of the obtained results with the experimental results is pointed out as well. On the other hand, the capability for experimental validation of the 2D PIC used by the authors is highlighted. This comment is dedicated to put one of codes, namely, the ONIX code in perspective concerning assumptions m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This was shown in our first paper [2] in the context of negative ion extraction and was more systematically illustrated in our following papers [3,4]. This point is well known by the plasma simulation community and it is surprising that the authors of the comment and of the criticized papers (see [1] and references therein) used mesh sizes much larger than the Debye length, their argument being that the number of mesh points must be limited in order to carry out 3D simulations. Moreover the method of injection of the plasma particles in the simulation domain was not correct in these papers, as shown in [2,3], and led to non-physical results.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…This was shown in our first paper [2] in the context of negative ion extraction and was more systematically illustrated in our following papers [3,4]. This point is well known by the plasma simulation community and it is surprising that the authors of the comment and of the criticized papers (see [1] and references therein) used mesh sizes much larger than the Debye length, their argument being that the number of mesh points must be limited in order to carry out 3D simulations. Moreover the method of injection of the plasma particles in the simulation domain was not correct in these papers, as shown in [2,3], and led to non-physical results.…”
mentioning
confidence: 70%
“…-We showed that inappropriate choice of mesh size in the PIC simulations can lead to erroneous conclusions. In the simulation results of the authors of the comment (see [1] and references therein), it appears that negative ions are not extracted from a quasineutral plasma behind a meniscus, but rather from the tips of the chamfered grid apertures where the electric field was sufficiently large to directly (i.e. without space charge neutralization) extract a large negative ion current density from the cesiated surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No numerical convergence analysis had been performed in these studies. As a consequence, this triggered a debate in the negative ion extraction modeling community regarding whether or not one must strictly respect the numerical constraints of explicit PIC schemes 140,141 .…”
Section: Extraction Of Negative Ionsmentioning
confidence: 99%
“…The topological structure of the magnetic field, especially the magnetic deflection field in EG, plays an important role in the numerical results. Small changes in magnetic field intensity or topological structure can greatly change the extracted electron current, and the correlation of simulation results can only be proposed based on a correctly established magnetic field structure [14].…”
Section: Open Access Edited Bymentioning
confidence: 99%